Metabolite profiling of Ipomoea aquatica at different growth stages in correlation to the antioxidant and alpha-glucosidase inhibitory activities elucidated by H-1 NMR-based metabolomics - Lawal, Umar; Mediani, Ahmed; H., Maulidiani; Shaari, Khozirah; Ismail, Intan Safinar; Khatib, Alfi; Abas, Faridah (Elsevier, 2015)
tIpomoea aquatica Forsk is a green leafy vegetable that is a rich source of secondary metabolites, vitaminsand amino acids with many health benefits. Proton Nuclear Magnetic Resonance (1H NMR) spectroscopywas combined with multivariate data analyses to distinguish Ipomoea aquatica samples at different devel-opmental stages. A principal component analysis (PCA) of Ipomoea leaves provides clusters based on thedifferent developmental stages by combining principal components PC1 and PC2 with a total varianceof 65.1%. A loading plot analysis revealed that the initial stages (weeks 3 and 4) showed comparativelylow contents of phenolic and organic acids, such as citric and maleic acid; the latter stages (weeks 5and 6) exhibited higher glucose and phenolic compound contents. The sugar, phenolic compound andorganic acid contents increased based on the developmental stage of the Ipomoea aquatica. The latentstructures were projected using a partial least squares (PLS) model to predict the biological activity of theIpomoea extracts based on their1H NMR spectra. The results of this study indicate that1H NMR-basedmetabolomics data could be used to discriminate the different developmental stages and to predict thebiological activities of Ipomoea leaves. The present study may be applied when monitoring the quality offruits and vegetables.